2015
DOI: 10.1016/j.rbr.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da força de preensão em ratos Wistar, normais e obesos, submetidos à natação com sobrecarga após compressão do nervo mediano

Abstract: The swimming exercise with overload has not been effective in promoting improvement in muscle grip strength after compression injury of the right median nerve in control and in obese-MSG rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The evaluations were used to observe the evolution of the lesion and the form of treatment used. In each evaluation, the test was repeated three times and the mean value of the repetitions was used ( Coradinia et al, 2015 ). Other evaluations were carried out during the experiment: 2nd EV, 3rd PO, pretreatment; 3rd EV, 3rd PO, post treatment; 4th EV, 7th PO, post treatment; 5th EV, 8th PO, pretreatment; 6th EV, 14th PO, after treatment; 7th EV, 21st PO, posttreatment; 8th EV, 22nd PO, euthanasia of the animals and collection of the muscles.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluations were used to observe the evolution of the lesion and the form of treatment used. In each evaluation, the test was repeated three times and the mean value of the repetitions was used ( Coradinia et al, 2015 ). Other evaluations were carried out during the experiment: 2nd EV, 3rd PO, pretreatment; 3rd EV, 3rd PO, post treatment; 4th EV, 7th PO, post treatment; 5th EV, 8th PO, pretreatment; 6th EV, 14th PO, after treatment; 7th EV, 21st PO, posttreatment; 8th EV, 22nd PO, euthanasia of the animals and collection of the muscles.…”
Section: Methodsmentioning
confidence: 99%
“…However, other studies have demonstrated delays in functional recovery from this type of exercise 8 or no effect on muscle strength, 10 and because of the slow regeneration process, problems such as inadequate nerve reinsertion and nerve function inefficiency are possible, impacting directly the final result. 1 This denotes the need for research about the effect of physical exercise on nerve repair and its association with auxiliary procedural substances.…”
Section: Introductionmentioning
confidence: 98%